Weather and Age Ratios of Northern Bobwhites in South Texas - Fred S. Guthery; Jeffery J. Lusk; David R. Synatzske; James Gallagher; Stephan J. DeMaso (National Quail Symposium Proceedings, 2017)
Understanding the effects of weather on quail reproduction in semiarid environments requires simultaneous consideration of temperature and precipitation data. Therefore, we used neural modeling to assess the interactive effects of summer (Jun–Aug) temperatures (monthly means of daily maxima) and seasonal precipitation (totals) on age ratios (juvenile/adult) of northern bobwhites (Colinus virginianus) in south Texas based on data collected during 1940–97 (n = 35, 23 years missing). Age ratios increased with June temperature. Ratios were insensitive to mean maximum daily temperature in July up to 36 C, when they began to decline rapidly. Ratios were insensitive to August temperatures. Ratios increased in an asymptotic manner with fall (Sep–Nov), spring (Mar–May), and summer precipitation, and were least sensitive to fall precipitation and most sensitive to spring precipitation. Based on our analysis, temperature and precipitation influenced bobwhite production in a complex, nonlinear manner that seemed to contain thresholds and asymptotes. Low temperatures can ameliorate the negative effects of drought, and high temperatures can suppress the positive effects of precipitation. The apparent asymptotic effect of precipitation, given temperature, illustrates that assumed linearity between precipitation and production may lead to errors of interpretation and expectation for production in a particular year.
Keywords: age ratio; Colinus virginianus; neural modeling; northern bobwhite; precipitation; production; reproduction; temperature; Texas; weather